Amniotic mesenchymal stem cells attenuate diabetic cardiomyopathy by inhibiting pyroptosis via modulation of the TLR4/NF-κb/NLRP3 pathway - Zhou, Xuan; Xing, Shaoliang; Zhang, Lina; Lu, Jungu; Li, Deming; Wang, Yating; Ma, Yuhang; Chang, Weiqin; Su, Manman (Frontiers in Cell and Developmental Biology, 2025)
Diabetic cardiomyopathy (DCM) is a specific type of cardiac dysfunction in diabetic patients, currently has no effective therapies. The TLR4 signaling pathway, activated through MyD88 and NF-κB, plays a critical role in DCM by triggering the release of pro-inflammatory cytokines and promoting pyroptosis through NLRP3 inflammasomes. Additionally, the TGF-β/Smad signaling pathway drives myocardial fibrosis, further compromising cardiac function. Recently, amniotic mesenchymal stem cells (AMSCs) have emerged as a promising therapeutic option due to their ease of access, low immunogenicity, and ability to differentiate into multiple cell types. In this study, a DCM mouse model was treated with AMSCs via tail vein injection every 2 weeks for four doses. Evaluations included glucose tolerance tests, echocardiography, serum analysis, and histopathological and molecular assessments. Results showed AMSCs improved pancreatic function, reduced blood glucose, and enhanced insulin secretion. Cardiac function and morphology improved, with reduced inflammation. Molecularly, AMSCs inhibited pyroptosis via TLR4/NF-κB/NLRP3 pathway suppression and reduced fibrosis through TGF-β/Smad modulation. These findings indicate AMSCs alleviate DCM cardiac dysfunction and pyroptosis, primarily by inhibiting the TLR4/NF-κB/NLRP3 pathway. The study underscores AMSCs as a promising therapeutic strategy for DCM, warranting further clinical exploration.